ANALISIS PELAKSANAAN PROMOSI PRODUK BETON SIAP PAKAI PADA PT. MITRA BETON MANDIRI PEKANBARU - Reza Junaidi; Lie Othman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Our is one of the elements from mix marketing (markeing mixed), besidethe determination selling, product, and distribution. Our very influential tocompany to achieve a maximum sales volume, because even though productsoffered is great, relatively cheap and easy to get, if not accompanied by our good,then the level sales would not suffice. Because the number of companies areengaged in that period, the company should be careful in order to carry out ourproducts concrete ready-to-use PT. Mitra Beton Mandiri Pekanbaru.Number of sample as many as 29 people, where population is used as amodel. The reason the taking of population as samples or use techniques censuselement because the population is relatively low. Results of research proceduresproduct promotion concrete ready to be used in PT. Mitra Beton MandiriPekanbaru in this advertising, sales private, publicity, our sales have done withgood.Key words : Promotion, the product Concrete ready-to-use, PT Mitra BetonMandiri Pekanbaru